The Influence of Accountability, Work Experience and Professionalism on The Quality of The Quality of The Work of Auditors - Sihol Marito Simorangkir; Jonathan Dubery Bukit; Keumala Hayati (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
The study was conducted aimed at examining the effect of accountability, work experience, and professionalism on the quality of auditor performance. auditors are required to have a high level of accountability because the auditor will present financial statements that must be accountable by himself. In addition to having a high accountability the auditor should also have good work experience so that the auditor can convey a logical and logical understanding of the errors contained in the financial statements. And auditors also require high professionalism so that auditors can carry out professional and good tasks. The object of research is the auditor who is working at the North Sumatra BPKP Office. The data is 70 respondents. The sampling method is the saturated sample technique. Analyze the data using validity, reliability and linear regression tests. And the results of the study prove that accountability has an influence on the quality of the work of the auditor, while work experience and professionalism do not have an influence on the quality of the work of the audiores.